The potential consequences of 'bee washing' on wild bee health and conservation. (August 2022) - Colla, Sheila R.
Abstract: Concern around declining bee populations globally has become an environmental issue of mainstream importance. Policymakers, scientists, environmental non-government organizations, media outlets and the public have displayed great interest in conservation actions to support pollinators. As with many environmental causes, green washing, or in this case 'bee washing', has become rampant. Bee washing can lead to multiple negative consequences, including misinformation, misallocation of resources, increasing threats and steering public understanding and environmental policy away from evidence-based decision-making. Here I will discuss the multiple potential consequences of bee washing on efforts to conserve declining wild bees and promote wild bee health. Graphical abstract: Image 1 Highlights: Concern around declining bee populations globally has become an environmental issue of mainstream importance. Policymakers, scientists, environmental non-government organizations, media outlets and the public have displayed interest in conservation action to support pollinators. 'Bee washing', has become rampant. Narratives and actions tend to focus on low-hanging fruit, actions which are easy to address and/or the selling of commercial items where industry benefits but the species of concern do not. Negative consequences include misinformation, misallocation of resources, increasing threats and steering environmental policy away from evidence-based decision-making.